A Study on the Relationship between Cash-flow and Financial Performance of Insurance Companies: Evidence from a Developing Economy - Sunday OGBEIDE; Babatunde AKANJI (Revista de Management Comparat International, 2017)
The study examines the relationship between cash flow and financial performance of insurance companies in a developing economy – Nigeria. Using time series data for the period 2009-2014, twenty seven listed insurance firms in Nigeria were selected as sample size. The study uses both descriptive and inferential statistics to determine the relationship among the variables. It also employs the series of diagnostic tests to ensure stability of the time series used as well as to ensure the model meets the assumption of ordinary list square. The findings reveal that cash flow was observed to determine insurance firms’ financial performance and is statistically significant. Cash flow from operating activities was observed to significantly increase financial performance of insurance companies in the period examined. Cash flow from financing activities was found to increase the financial performance of the sampled insurance firms, but was not statistically significant. The size of the insurance company did not increase the financial performance of the insurance firms and was also not statistically significant. The paper recommends that managers in insurance firm should regularly change the extent at which cash is spent to avoid negative cash flow position as well as financial crisis. Adequate investment appraisal is really a concern that insurance firms need to take into consideration when customers are taking up insurance coverage. The costs have to be weighed against the benefits accruable thereto.